Relationships among Team Trust, Team Cohesion, Team Satisfaction and Project Team Effectiveness as Perceived by Project Managers in Malaysia - Fung, Han-Ping (International Journal of Business, Economics and Management, 2014)
Today, more and more project teams are formed to achieve organizational objectives as organizations generally recognized the importance and benefits of project teams. There is a compelling reason to study what are the team outcome factors that can predict project team effectiveness as it is unclear whether these team outcome factors can yield the same result in project setting whereby there is resource and time constraint compare to normal work teams which are ongoing and operational in nature. This study has developed a research model underpinned on Cohen and Bailey (1997) Team Effectiveness Framework to empirically analyze some team outcome factors in which result showed that team trust is directly predicting team cohesion, team satisfaction and project team effectiveness. However, team cohesion is not directly predicting project team effectiveness but it is directly predicting team satisfaction. In turn, team satisfaction is directly and positively predicting project team effectiveness. In other words, team cohesion indirectly predicting project team effectiveness via team satisfaction. Discussion, limitation and conclusion are also included in this article.